The changes of radiotherapy in Lithuania: infrastructure, utilization rate, and cost - Mineikytė, Ramunė; Janulionis, Ernestas; Atkočius, Vydmantas; Jaruševičius, Laimonas; Plieskienė, Aista; Gečas, Jonas (Acta medica Lituanica, 2016)
Background. The aim of this study was to evaluate radiation therapy (RT) productivity, capacity, and cost in Lithuania. Materials and methods. An electronic questionnaire was prepared and sent to the country’s RT centres. The data was collected for the years 2011–2014. The  early data of the  RT infrastructure was obtained from the QUARTS Project (2001). Results. In Lithuania the  external beam RT was applied to 32.6% of new cancer cases (non-melanomatous skin cancer and benign conditions were excluded). In 2014, RT was more frequently applied for breast and prostate carcinomas, 23 and 20%, respectively. The country owned 11 units of linear accelerators (linacs) and this accounts for 3.7 linacs per one million population. 3D conformal RT is the  standard approach in all four RT centres in Lithuania. IMRT practices were established in three centers and VMAT or stereotactic RT in two of them. 73% of linacs were capable of IGRT, while only 27% were equipped with CBCT. The average linac workload was 567 patients per year and showed a 10% decrease compared with the 2011 data. During a ten-year period, the average cost per patient for RT treatment increased 7.6 times – from EUR 129 to 974. The reimbursement system in Lithuania is not favourable for application of RT. Conclusions. During the recent thirteen years, RT services in Lithuania have dramatically improved, but we are still behind the average of European countries and benchmark rates. It is important to continue optimising the efficiency of RT services, and further evidence-based studies on RT infrastructure assessment and planning are needed.